Role of Probiotic Bacilli in Developing Synbiotic Food: Challenges and Opportunities - Szlufman, Carolina; Shemesh, Moshe (Frontiers in Microbiology, 2021)
The human body is inhabited by a vast diversity of probiotic microorganisms that could positively affect human physiology. Also, prebiotic food substances may induce probiotic species' symbiotic relationship through the successful establishment of commensal microbiota, whose connections with the host are multifaceted and multidirectional. As deliberated throughout this review, prebiotic and synbiotic foods contain the capability to stimulate numerous health characteristics in host organisms through various means. Predominantly, the normal microbiota fosters the digestion of food and may boost the innate and adaptive immune system's functionalities. Therefore, live probiotic bacteria, for instance, probiotic Bacilli obtained together with prebiotic food, can help stimulate healthiness in humans. Thus, we discuss how certain dietary fibers may preserve the probiotic efficacy by serving as the scaffold for probiotic Bacilli to colonize them through forming symbiotic interactions. The fibers can essentially promote protection by encapsulating probiotic Bacilli against various environmental and physical stresses that might kill the free-living bacterial cells. Besides, these fibers would serve as prebiotic substances that would eventually be utilized for the proliferation of probiotic cells. It is believed that applying this conceptual idea will provide a novel platform towards developing probiotic and synbiotic foods, as discussed in this review.